2-Ethynyl-6-methylthieno[3, 2-b]thiophene as an efficient π spacer for porphyrin-based dyes. (November 2015) - Zhao, Huifang; Long, Jun; Luo, Xi; Zhao, Bin; Tan, Songting
Abstract: In this study, three donor-π-acceptor (D-π-A) type unsymmetrical porphyrin-based dyes have been designed and synthesized for dye-sensitized solar cells (DSSCs). The photophysical, electrochemical and photovoltaic properties of the dyes were successfully adjusted by using functionalized arylamines (triphenylamine or N, N-dimethyl-4-(acetylene)-aniline) as donor, porphyrin derivatives as conjugated π bridge, ethynyl-thiophene or ethynyl-thiophthene as π spacer and carboxylic acid as anchor group. Compared with the dye containing ethynyl-thiophene as π spacer, the dyes containing 2-ethynyl-6-methylthieno[3, 2- b ]thiophene as π spacer between the porphyrin macrocycle and the carboxylic acid anchoring group show broadened absorption spectra on TiO2 films and red-shifted absorption spectra in solution. The dye based on triphenylamine and 2-ethynyl-6-methylthieno[3, 2- b ]thiophene exhibited a power conversion efficiency (PCE) of 4.53% under simulated air mass 1.5 global sunlight. These results indicate that the introduction of 2-ethynyl-6-methylthieno[3, 2- b ]thiophene in the meso-positions of porphyrin dyes is an effective approach to improve the photovoltaic performance. Highlights: Three new D-π-A type unsymmetrical porphyrin dyes were synthesized. 2-Ethynyl-6-methylthieno[3, 2-b]thiophene as π spacer broadened the absorption. DyeBSF exhibited higher conversion efficiency than that ofSF andNSF .